Irrigated urban vegetable production in Ghana: microbiological contamination in farms and markets and associated consumer risk groups - Amoah P.; Drechsel P.; Abaidoo R. C; Henseler M. (IWA Publishing, 2023)
This article is published by IWA Publishing,2007